2014
DOI: 10.1002/cne.23576
|View full text |Cite
|
Sign up to set email alerts
|

Established monolayer differentiation of mouse embryonic stem cells generates heterogeneous neocortical‐like neurons stalled at a stage equivalent to midcorticogenesis

Abstract: Two existing and widely applied protocols of embryonic stem (ES) cell differentiation have been developed to enable in vitro generation of neurons resembling neocortical projection neurons in monolayer culture and from embryoid bodies. The monolayer approach offers advantages for detailed in vitro characterizations and potential mechanistic and therapeutic screening. We investigated whether mouse ES cells undergoing largely undirected neocortical differentiation in monolayer culture recapitulate progressive de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 82 publications
(162 reference statements)
1
27
0
Order By: Relevance
“…A slow-down in gene expression dynamics has been observed in previous studies of human cortical development (Bakken et al, 2016; Colantuoni et al, 2011). It is possible that our in vitro observations reflect similar changes occurring at equivalent ages in vivo, or that some extrinsic element necessary for continued development of these cells is missing from our protocol, as previous work has suggested that development is comparatively slow in vitro (Sadegh and Macklis, 2014). …”
Section: Discussionmentioning
confidence: 95%
“…A slow-down in gene expression dynamics has been observed in previous studies of human cortical development (Bakken et al, 2016; Colantuoni et al, 2011). It is possible that our in vitro observations reflect similar changes occurring at equivalent ages in vivo, or that some extrinsic element necessary for continued development of these cells is missing from our protocol, as previous work has suggested that development is comparatively slow in vitro (Sadegh and Macklis, 2014). …”
Section: Discussionmentioning
confidence: 95%
“…Utilizing iPSCs to generate neural tissue from patients with neurological diseases at scale can provide a better avenue with which to screen drugs targeting specific human diseases [75]. However, as mentioned above neurons produced in monolayers in the culture dish often lack developmental maturity [76, 77, 51]. Brain-chips taking advantage of unique co-culture geometries have successfully co-cultured human ES cell-derived neural progenitor cells, endothelial cells, mesenchymal stem cells, and microglia/macrophage precursors, allowing complex interactions reminiscent of the developing CNS [78].…”
Section: Bbb Modeling and Brain-chipsmentioning
confidence: 99%
“…Thus, the generation of CSMNs from familial ALS patient iPSCs may provide insight into the degeneration and preservation of these cells. It should be noted that upon careful examination, monolayer systems appear to exhibit stalled maturation of cortical subtypes in terms of inappropriate expression of laminar and postmitotic markers [51]. Impressively, the forebrain organoids generated by [25] harbor distinct cortical organization; and though an in-depth assessment regarding the existence of bona fide CSMNs in these organoids is yet to be reported, this culturing system provides promise towards the generation of this intricate cell type.…”
Section: Introductionmentioning
confidence: 99%
“…Midway through corticogenesis, post-mitotic SCPN identity is initially masked by transient co-expression of regulators of interhemispheric callosal projection neuron (CPN) development, including SATB2 (Alcamo et al, 2008;Britanova et al, 2008;Azim et al, 2009;Woodworth et al, 2012;Sadegh and Macklis, 2014;Leone et al, 2015). At later stages of maturation, SCPN discontinue expression of SATB2, and further resolve into diverse subpopulations of FEZF2-and CTIP2-expressing projection neurons with cortical area-and target-specific molecular identities, properties, and functional circuit Sadegh et al 4 connectivity (Woodworth et al, 2012;Custo Greig et al, 2013;Woodworth et al, 2016;Greig et al, 2016;Galazo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…ES/iPSC-based models of cortical differentiation are emerging as useful tools to investigate roles of chromatin modifications in cortical development (Tiberi et al, 2012;Juliandi et al, 2012). While protocols for directing cortical differentiation from ES/iPSC cells in systems ranging from monolayer cultures to organoids have succeeded in replicating some of the molecular characteristics of cortical development (Eiraku et al, 2008;Gaspard et al, 2008;Michelsen et al, 2015;Lancaster et al, 2013, Arlotta, 2018Pasca, 2018), the mature refinement of cortical subtypes is incomplete with these protocols; immature neurons become "stalled" at an mid-embryonic developmental stage (Sadegh and Macklis, 2014). These data suggest that ES-derived cortical cells are unlikely to have a sufficiently permissive molecular context for the precise refinement of SCPN identity.…”
Section: Introductionmentioning
confidence: 99%